Time spent gaming, device type, addiction scores, and well-being of adolescent english gamers in the 2021 Oxwell survey: latent profile analysis - Skripkauskaite, S; Fazel, M (JMIR Publications, 2022)
Background: The shift in the last decades to screen-based and increasingly web-based gaming activity has raised concerns about its impact on the development of children and adolescents. Despite decades of research into gaming and related psychosocial effects, the question remains how best to identify what degree or context of gaming may be a cause for concern.